Effect of the sense of coherence and associated factors in the quality of life of head and neck cancer patients - Laura Izabel Lampert BONZANINI; Eloisa Barbieri SOLDERA; Gabriela Barbieri ORTIGARA; Riéli Elis SCHULZ; Jessica Klöckner KNORST; Thiago Machado ARDENGHI; Kívia Linhares FERRAZZO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The sense of coherence (SOC) is a measure of global orientation regarding the ability of individuals to cope with stressful situations. The aim of the present study was to evaluate the association between SOC and quality of life (QoL) and clinical and sociodemographic characteristics among survivors of oral, oropharynx, hypopharynx, or larynx cancer. A cross-sectional study was conducted with 90 cancer patients in follow up at the Santa Maria University Hospital in southern Brazil who had completed conformal 3D radiotherapy at least three months earlier. QoL was assessed using the University of Washington Quality of Life (UW-QOL) questionnaire and SOC was measured using the Brazilian version of the SOC-13 questionnaire. Data on socio-demographic characteristics and the disease were obtained from patients' charts. Oral clinical conditions were also evaluated. Associations between exploratory variables and mean UW-QOL scores were evaluated through Poisson regression and the results were presented as rate ratios (RR) and 95% confidence intervals (CI). The mean overall UW-QOL score was 67.90 (± 18.71). Moderate and high SOC scores were associated with higher mean UW-QOL scores, that is, individuals with a stronger SOC demonstrated better QoL, (p < 0.05). Regarding the clinical variables, individuals with advanced stage cancer and those with hyposalivation and trismus had poorer QoL (p < 0.05). Patients with a greater SOC reported a better quality of life. Our findings show the importance of focusing on psychosocial factors, which can alleviate the impact caused by the disease and improve the QoL of these patients.